2015
DOI: 10.1074/jbc.m114.627968
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Phosphatidic Acid-Protein-tyrosine Phosphatase D2 Axis Is Essential for ERBB2 Signaling in Mammary Epithelial Cells

Abstract: Background:The role of protein-tyrosine phosphatases (PTP) in ERBB2 signaling is undefined. Results: Phosphatidic acid (PA) activated PTPD2; inhibition of PA production or PTPD2 expression attenuated ERBB2-mediated morphological changes in mammary epithelial cells. Conclusion: The PLD2-PTPD2 axis is required for ERBB2 signaling. Significance: PA-regulated PTPD2 activity is a novel, positive element of ERBB2 signaling, which may offer a new therapeutic strategy in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Our laboratory performed RNAi-mediated loss-of-function screens to test the effects of suppressing systematically the expression of PTP family members in threedimensional cell culture models. We identified several PTPs as novel negative and positive regulators of HER2 signaling in the control of cell polarity, migration, and invasion (Lin et al 2011;Ramesh et al 2015). Interestingly, only PTPN23 was shown to inhibit mammary epithelial cell motility and invasion in a HER2-independent manner by impairing the integrity of adheren junctions through regulating the phosphorylation status of E-cadherin and β-catenin (Lin et al 2011).…”
mentioning
confidence: 99%
“…Our laboratory performed RNAi-mediated loss-of-function screens to test the effects of suppressing systematically the expression of PTP family members in threedimensional cell culture models. We identified several PTPs as novel negative and positive regulators of HER2 signaling in the control of cell polarity, migration, and invasion (Lin et al 2011;Ramesh et al 2015). Interestingly, only PTPN23 was shown to inhibit mammary epithelial cell motility and invasion in a HER2-independent manner by impairing the integrity of adheren junctions through regulating the phosphorylation status of E-cadherin and β-catenin (Lin et al 2011).…”
mentioning
confidence: 99%
“…In absence of Tie-2, VE-PTP inhibition destabilized endothelial junctions suggesting a functional role for Tie-2 in barrier regulation in the absence of VEcadherin [71]. In this study, we identified a novel role for PTPN14, a PLD2 dependent non-receptor PTP [24], in regulating thrombin-induced VEcadherin stabilization in AJs in human lung ECs. Our study clearly demonstrates that the activity of PTPN14 is essential for stabilization of VE-cadherin at AJs through dephosphorylation of VE-cadherin during thrombin-induced endothelial barrier recovery of lung ECs.…”
Section: Discussionmentioning
confidence: 72%
“…PTPN14 was identified as a major phosphatase of epithelial and endothelial cell AJs and dominant negative PTPN14 (Pez) mutant enhanced cell motility suggesting potential regulation by PTPN14 through its action on cell-cell adhesion (73). Interestingly, PTPN14 is a positive regulator of ERBB2 signaling in mammary epithelial cells, which is dependent on PLD2 dependent (24) and in cancer cells PTPN14 promoted proliferation and migration through the regulation of Hippo/YAP signaling pathway (74).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations